Controllable Synthesis of Fluorescent Carbon Dots and Their Detection Application as Nanoprobes - Yang, Zhi; Li, Zhaohui; Xu, Minghan; Ma, Yujie; Zhang, Jing; Su, Yanjie; Gao, Feng; Wei, Hao; Zhang, Liying (Nano-Micro Letters, 2013)
Carbon dots (CDs), as a new member of carbon nanomaterial family, have aroused great interest since their discovery in 2004. Because of their outstanding water solubility, high sensitivity and selectivity to target analytes, low toxicity, favorable biocompatibility, and excellent photostability, researchers from diverse disciplines have come together to further develop the fundamental properties of CDs. Many methods for the production of CDs have been reported, therein, hydrothermal and solvothermal technology needs simple equipments, and microwave synthesis needs less reaction time, hence these methods become current common synthesis methods, in which many precursors have been applied to produce CDs. Due to their excellent fluorescence, CDs have made impressive strides in sensitivity and selectivity to a diverse array of salt ions, organic/biological molecules and target gases. The development of CDs as nanoprobes is still in its infancy, but continued progress may lead to their integration into environmental and biological applications. Hydrothermal, solvothermal, and microwave synthesis of fluorescent carbon dots and their detection applications as nanoprobes in salt ions, organic/biological molecules, and target gases will be reviewed.